(3JMQjQ cJGH GdcQI GdeJMQcI dGhWhdhbSs - (3KGHJ Hf bQIs; (3KGhPhSjhSs
(3ChdgG (B:s
(3HYO GdOjHGLI GdUOQ HGdfbW GdJj JJMQc MQcI eYJOdI gj GdJj JSjQ aj CReGf eJSGhjI s
(3BNQgG (B:s
(3hcGf GdSWM eGFdkG gPG Nda eQcR GdcQI dGZjQ aEPf cd hGMOI ef OGFQJj YXjeI s
(3Vef eLehY , JQJjHgG (B: 6s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdj (B(1930) s
Keywords: (3eJaQbGJs